2008
DOI: 10.1038/bmt.2008.370
|View full text |Cite
|
Sign up to set email alerts
|

Height growth during adolescence and final height after haematopoietic SCT for childhood acute leukaemia: the impact of a conditioning regimen with BU or TBI

Abstract: We compared the impact of a conditioning regimen with BU (n=16) or fractionated TBI (n=42) on height growth during adolescence and final height (FH), in 58 adults transplanted for acute leukaemia before adolescence (younger than 9 for girls and 11 for boys, and prepubertal). Heights were measured at three key periods, that is, transplantation, before adolescence, and FH, and compared using height standard deviation score (SDS) and cumulative change in SDS. The influence of the conditioning regimen was assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
2
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 25 publications
3
25
2
4
Order By: Relevance
“…DOI: 10.1159/000486034 In our cohort, SS occurred in patients conditioned with busulfan-containing regimens at a rate similar to that seen following TBI, as reported by Bernard et al [25]. Although busulfan is less toxic than TBI-containing regimens, it may adversely affect growth by its toxic effect on gonads leading to impaired gonadal function and dysregulation of interactions between sex hormones and GH, with subsequent altered peripubertal growth.…”
Section: Discussionsupporting
confidence: 53%
“…DOI: 10.1159/000486034 In our cohort, SS occurred in patients conditioned with busulfan-containing regimens at a rate similar to that seen following TBI, as reported by Bernard et al [25]. Although busulfan is less toxic than TBI-containing regimens, it may adversely affect growth by its toxic effect on gonads leading to impaired gonadal function and dysregulation of interactions between sex hormones and GH, with subsequent altered peripubertal growth.…”
Section: Discussionsupporting
confidence: 53%
“…Besides the well-known damage to puberty and gonadal function, 3 we confirm a consequent impact on growth, as previously noted. 28 Moreover, BU increased widely the risk of overweight (OR ¼ 3.9). Previous studies have reported the changes in BMI (over-or underweight) induced by HSCT.…”
Section: Health Status After Hct F Bernard Et Almentioning
confidence: 99%
“…The literature contains a number of studies about factors that adversely affect growth in children treated for AL (age at the time of AL treatment, irradiation dose and fraction size, and so on). 3,6,[9][10][11][12][13][14] By contrast, only a few studies have evaluated the impact of GH replacement therapy on growth rate and FH in these children. 1,2,7,[15][16][17] A better understanding of the factors influencing response to GH will allow the identification of patients who can benefit from appropriate hormonal replacement therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The growth and growth hormone (GH) deficiency have been observed in children after haematopoietic SCT (HSCT) with TBI [1][2][3][4][5] and those previously undergoing central nervous system irradiation (CI) to treat acute leukaemia (AL). [1][2][3][5][6][7] Conditioning regimen chemotherapy and irradiation are often superimposed on the 'standard' therapies, which may compromise pubertal development and final height (FH) in their own right.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation